2015
DOI: 10.1002/pen.24073
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of polylactic acid/polyethylene glycol (PLA/PEG) porous scaffold by supercriticalCO2foaming and particle leaching

Abstract: PLA/PEG/NaCl blends were melt‐blended followed by gas foaming and particle leaching process to fabricate porous scaffold with high porosity and interconnectivity. A home‐made triple‐screw compounding extruder was used to intensify the mixability and dispersion of NaCl and PEG in the PLA matrix. Supercritical carbon dioxide was used as physical blowing agent for the microcellular foaming process. Sodium chloride (NaCl) was used as the porogen to further improve the porosity of PLA scaffold. This study investiga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(22 citation statements)
references
References 47 publications
0
21
0
1
Order By: Relevance
“…Owing to biocompatibility, biodegradability, and relatively high mechanical properties, polylactic acid (PLA, an FDA approved biopolymer) has been widely adopted for biomedical applications [23]. Although both PCL and PLA are linear aliphatic polyesters, the difference on molecular compositions makes PCL a more flexible, hydrophobic, and crystalline polymer that is slower to degrade than PLA; on the other hand, PLA has higher stiffness/modulus and strength than PCL [24].…”
Section: Introductionmentioning
confidence: 99%
“…Owing to biocompatibility, biodegradability, and relatively high mechanical properties, polylactic acid (PLA, an FDA approved biopolymer) has been widely adopted for biomedical applications [23]. Although both PCL and PLA are linear aliphatic polyesters, the difference on molecular compositions makes PCL a more flexible, hydrophobic, and crystalline polymer that is slower to degrade than PLA; on the other hand, PLA has higher stiffness/modulus and strength than PCL [24].…”
Section: Introductionmentioning
confidence: 99%
“…The scaffold material plays a vital role in the development of engineered bone, and it should possess a highly porous structure that promotes cell attachment, proliferation and bone tissue formation and mineralization. Numerous methods have been developed to introduce porosity into scaffold materials, including solvent casting-particulate leaching, 5 supercritical CO 2 gas foaming and particulate leaching, 6 emulsion freezing/freeze-drying, 7 and emulsion templating. The advantage of synthetic polymer scaffolds is their customizable chemical, physical and mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported the blending of PLLA with biopolymers, which have a plasticizing effect for biomedical applications. Chen et al (2015) report the preparation of a porous scaffold from blend of PLLA and poly(ethylene glycol) (PEG) by supercritical CO2 foaming and particle leaching. The addition of PEG to the PLLA matrix has a plasticizing effect on the PLLA, indicated by the decrease in Tg in it.…”
Section: Introductionmentioning
confidence: 99%